The Old and New Visions of Biased Agonism Through the Prism of Adenosine Receptor Signaling and Receptor/Receptor and Receptor/Protein Interactions - Franco, Rafael; Rivas‐Santisteban, Rafael; Reyes-Resina, Irene; Navarro, Gemma (Frontiers in Pharmacology, 2021)
Biased signaling is a concept that has arisen in the G-protein-coupled receptor (GCPR) research field, and holds promise for the development of new drug development strategies. It consists of different signaling outputs depending on the agonist chemical structure. Here we review the most accepted mechanisms for explaining biased agonism, namely the induced fit hypothesis and the key/lock hypothesis, but we also consider how bias can be produced by a given agonist. In fact, different signaling outputs may originate at a given receptor when activated by, for instance, the endogenous agonist. We take advantage of results obtained with adenosine receptors for explaining how such mechanism of functional selectivity is depending of the context, being receptor-receptor interactions (heteromerization) both one of the most relevant for mammalian homeostasis and one of the most studied. Considering all the possible mechanisms underlying functional selectivity is instrumental to optimize the selection of biased agonists for GPCR-centered drug design.